Genetics and genetic counseling in psychiatry: Results from an opinion survey of professionals and users. Issue 8 (29th June 2019) - Martorell, Lourdes; Sanfeliu, Annabel; Blázquez, Ana; Lojo, Elia; Cortés, Maria José; de Pablo, Joan; Vilella, Elisabet
Abstract: Background: The heritability of several psychiatric disorders is high, and specific at‐risk variants have been identified. Therefore, genetic counseling and genetic testing can be prescribed to some psychiatric patients, but these services are not standardized for most of the population. The aims of the study were to gather opinions from mental health professionals and users regarding (a) the genetics of psychiatric disorders and (b) the usefulness of a genetic counseling unit in psychiatry. Methods: The survey was conducted in the province of Tarragona (Spain), and we analyzed 152 valid questionnaires from professionals and 959 from users. Results: Sixty‐one percent of professionals strongly believed that psychiatric disorders have a genetic basis, and 59% rated a genetic counseling unit in psychiatry as very or extremely useful. However, only a few professionals reported that patients asked them about the genetics of their diseases (12%) or the possibility of transmitting the disease to offspring (19%). Forty‐seven percent of users strongly believed that psychiatric disorders have a genetic basis, 30% responded that they talked with their families about the genetics of their diseases, and 43% were worried about transmitting the disease to offspring; however, only 14% reported that their psychiatrist had talked to them about this topic. Remarkably, 80% of users would consider a genetic counseling unit very or extremely useful. Conclusions: The present study showed that mental health professionals were more aware of the genetic basis of psychiatric disorders than users, and both considered the implementation of a genetic counseling service very useful. Abstract : Genetic counseling and genetic testing could be prescribed to some psychiatric patients, but these services are not standardized for most of the population. We have collected the opinion of 152 mental health professionals and 959 users through a survey regarding the genetics of psychiatric disorders and the usefulness of a genetic counseling unit in psychiatry. The present study showed that mental health professionals were more aware of the genetic basis of psychiatric disorders than users were, and both considered the implementation of a genetic counseling service very useful